MR-MPS-SW:2016 and CMMI-DEV v2.0: an Initial Experience of Harmonization - da Rocha, Ana Regina C.; Zabeu, Ana Cecilia; Machado, Cristina Filipak (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Many organizations need to base their process improvement effort on more than one model. In Brazil organizations involved with software development frequently adopt this multi-model approach using the MR-MPS-SW and the CMMI-DEV models. In order to support these organizations previous work carried out the mapping of these two models. The advent of version 2.0 of CMMI-DEV model has become necessary to conduct a new mapping. This article describes an initial experience of mapping MR-MPS-SW:2016 and CMMI-DEV v 2.0, which showed the feasibility of the harmonization of the two models.